Replacing an 'In-Person' Global Health Annual Conference With a Virtual Format: A Case Study from the Consortium of Universities for Global Health. Issue 1 (31st March 2022) - Li, Melissa W.; Martin, Keith; Kolars, Joseph C.
Background: Beginning in 2020, the COVID pandemic disrupted many planned annual meetings that relied on travel to a destination for sharing scholarship, networking, and planning future collaborations. As with many organizations, the Consortium of Universities for Global Health (CUGH) began exploring the utilization of a virtual platform on which to conduct the annual conference. Objective: We sought to understand the value of conducting an annual conference virtually and to evaluate the added benefit of utilizing a learning management system. Methods: Routinely collected registration data was used for the CUGH 2021 annual conference, which was completely virtual, and compared to in-person registration data from prior years. In addition, tracking and engagement data from a learning management system was reviewed to understand participation. Findings: The virtual conference attracted the greatest number of registrations, from the largest number of countries since the organization began in 2008. Analyzing the engagement of participants with specific sessions through the on-line learning management system allowed a deeper understanding of the popularity and value of topics. Conclusion: A virtual format is an efficient and effective venue for scholarly conferences. The additional information gained from an on-line learning management system can provide valuable information for future conference planning.